Network-Based Delivery and Sustainment of Evidence-Based Prevention in Community-Clinical Partnerships Addressing Health Equity: A Qualitative Exploration - Ramanadhan, Shoba; Daly, James; Lee, Rebekka M.; Kruse, Gina R.; Deutsch, Charles (Frontiers in Public Health, 2020)
Background: Increased delivery of evidence-based preventive services can improve population health and increase health equity. Community-clinical partnerships offer particular promise, but delivery and sustainment of preventive services through these systems face several challenges related to service integration and collaboration. We used a social network analysis perspective to explore a) the range of contributions made by community-clinical partnership network members to support the delivery of evidence-based preventive services and b) important influences on the ability of these partnerships to sustain service delivery. Methods: Data come from an implementation evaluation of the Prevention and Wellness Trust Fund initiative, which supported nine Massachusetts communities to coordinate delivery of evidence-based prevention and address inequities in hypertension, pediatric asthma, falls among older adults, or tobacco use. In 2016, we conducted semi-structured interviews with a) leadership teams representing nine community-level partnerships and b) practitioners from four high-implementation partnerships (n=23). We managed data using NVivo11 and utilized a framework analysis approach. Results: Key network contributions for delivery of evidence-based preventive services included creating referrals, delivering services, providing links to community members, and administration and leadership. Less emphasized contributions included wraparound services, technical assistance, and venue provision. Implementers from high-implementation partnerships also highlighted contributions such as program adaptation, creating buy-in, and sharing information to improve service delivery. Expected drivers of program sustainability included the ability to develop a business case, ongoing network facilitation, technology support, continued integrated action, and sufficient staffing to maintain programming. Conclusion: The study highlights the need to take a long-term, infrastructure-focused approach when designing community-clinical partnerships. Strategic partnership composition, including identifying sources of necessary network contributions, in conjunction with efforts from the outset to link systems, align effort, and build a long-term funding structure can support the required coordinated action around preventive services needed to improve health equity.